2008
DOI: 10.1371/journal.pone.0001713
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric Tartrate Resistant Acid Phosphatase Induces Insulin Sensitive Obesity

Abstract: BackgroundObesity is associated with macrophage infiltration of adipose tissue, which may link adipose inflammation to insulin resistance. However, the impact of inflammatory cells in the pathophysiology of obesity remains unclear. Tartrate resistant acid phosphatase (TRAP) is an enzyme expressed by subsets of macrophages and osteoclasts that exists either as an enzymatically inactive monomer or as an active, proteolytically processed dimer.Principal FindingsUsing mice over expressing TRAP, we show that over-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 76 publications
4
40
0
2
Order By: Relevance
“…Moreover, TRAP is overexpressed in the adipose tissue of obese humans. 10 The cellular origin of TRAP in the adipose tissue is not fully settled, although total TRAP and TRAP 5a co-localized with the monocyte/macrophage marker CD68. 10 However, as CD68 is also expressed by other cell types besides macrophages, 32 we determined the expression pattern of TRAP in different cells of the human adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, TRAP is overexpressed in the adipose tissue of obese humans. 10 The cellular origin of TRAP in the adipose tissue is not fully settled, although total TRAP and TRAP 5a co-localized with the monocyte/macrophage marker CD68. 10 However, as CD68 is also expressed by other cell types besides macrophages, 32 we determined the expression pattern of TRAP in different cells of the human adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…10 The cellular origin of TRAP in the adipose tissue is not fully settled, although total TRAP and TRAP 5a co-localized with the monocyte/macrophage marker CD68. 10 However, as CD68 is also expressed by other cell types besides macrophages, 32 we determined the expression pattern of TRAP in different cells of the human adipose tissue. Separation of different cell types by immunodepletion/selection, followed by TRAP mRNA quantification revealed that TRAP is highly expressed per cell in ATMs compared with mature adipocytes, adipocyte progenitor cells, endothelial cells and cells negative for CD34, CD14 and CD31 in both lean and obese subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other genes of the list, such as HLA-DR, M130, CDSIGN and IL-10 (also known as IL10), have been shown to be highly expressed in human ATMs [22,23]. TRAP is highly expressed in adipose tissue of obese individuals where it is secreted from ATM [42]. Second, we investigated the association between ATMspecific gene expression levels and clinical variables in paired SAT and VAT samples from four thoroughly phenotyped groups of lean, overweight, obese and the metabolic syndrome individuals.…”
Section: Discussionmentioning
confidence: 99%